Proactive order monitoring in available-to-promise chain : Possibilities in material availability reporting - Lindblom, Miro Kalervo Johannes (My University, 2021)
With complex supply chains, enterprise resource planning solutions and extended manufacturing execution systems have a significant role in managing supply chains. Functionalities, such as advanced available-to-promise and supply chain control tower, enable clarity and flow of information through the supply chains and require real-time data and global control mechanisms in supply chain management. The objective of this thesis research was to find out the requirements for a digital tool in the proactive purchase order monitoring process. The second objective was to find out the capabilities of the current tool in use. The third objective was to map out potential tools in the proactive purchase order monitoring process to compare with the current one. The research was done as a case study with emphasis put on direct and participant observations. In the literature review, the literature related to available-to-promise, extended manufacturing execution system and supply chain control towers was reviewed to form a clear picture of how different tools are restricted for a specific use and what platform could be utilized to build a tool for proactive order monitoring. The three topics were also reviewed to see the future requirements of supply chain management tools and how the tools built now could fit in the 4th industrial revolution. The literature review reviewed design research and requirement engineering to form the requirements for the potential new tool according to the standards. As a result, a suggestion on an improved tool for proactive order monitoring was given. The suggested tool was also seen as a step towards a supply chain control tower process. A proposal was also given for further research on the capabilities and actions required by the case company to reach the readiness to utilize centralized supply chain management tools.

Monimutkaisten toimitusketjujen myötä toiminnanohjausjärjestelmät ja laajennetut MES-järjestelmät ottavat suurempaa roolia toimitusketjujen hallinnassa. Toiminnallisuudet kuten advanced ATP ja keskitetyn toimitusketjujen hallinnan control tower antavat mahdollisuuksia lisätä läpinäkyvyyttä ja tietovirtaa toimitusketjuissa, mutta vaativat reaaliaikaisen datan ja globaalit ohjausmekanismit tuotantoketjujen hallintaan. Opinnäytetyölle asetetut tavoitteet olivat löytää vaatimukset proaktiivisessa ostotilausten valvonnassa käytettävälle digitaaliselle työkalulle. Toinen tavoite oli selvittää nykyisen digitaalisen työkalun kapasiteetti. Kolmas tavoite oli kartoittaa potentiaaliset työkalut, jotka soveltuvat proaktiiviseen ostotilausten valvontaan, jotta niitä voidaan vertailla nykyiseen työkaluun. Tutkielma tehtiin case-menetelmällä, jossa painotettiin suoria sekä osallistavia havaintoja. Kirjallisuuskatsauksessa käytiin läpi kirjallisuutta available-to-promise-menetelmään sekä sille rakennettuihin järjestelmiin, laajennettuun MES-työkaluun sekä keskitetyn toimitusketjujen hallinnan control toweriin, jotta proaktiivisessa ostotilausten valvonnassa käytettävien työkalujen rajotteet sekä suositeltava alusta saataisiin selville. Tämän lisäksi kolmea aihetta käytiin läpi, jotta neljännen teollisen vallankumouksen tuomat vaatimukset toimitusketjujen hallinnassa käytettäville digitaalisille ratkaisuille saataisiin selville. Kirjallisuuskatsauksessa käytiin läpi suunnitteluteoriaa sekä vaatimusten rakentamista, jotta proaktiiviseen ostotilausten valvontaan käytettävä työkalu vastaisi sekä vaatimuksia että standardeja. Opinnäytetyön tuloksena muodostui ehdotus uudesta työkalusta toimitusketjujen hallinnassa käytettäville digitaalisille ratkaisuille. Ehdotettu työkalu nähtiin myös askeleena kohti keskitetyn toimitusketjujen hallinnan control toweria, joten lopptuloksena annettiin myös ehdotelma jatkotutkimukselle case yrityksen kyvystä sekä tarvittavista toimista varmistamaan kyvykkyys ottaa keskitetyn toimitusketjujen hallinnan control tower käyttöön tulevaisuudessa.
Keywords: supply chains; purchasing; enterprise resource planning systems; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management